PRESUPPOSITION ANALYSIS OF CHARACTER’S UTTERANCES IN CAMP ROCK MOVIE - Melly, Melly; Ambalegin, Ambalegin (Fakultas Ilmu Budaya, Universitas Mulawarman, 2022)
This descriptive qualitative research aimed to discover different types of presupposition occurred in the Camp Rock movie. To sort the data into categories according to the types of presupposition, the theory of Yule (1996) was applied. Existential presupposition, factive presupposition, lexical presupposition, structural presupposition, non-factive presupposition, and counterfactual presupposition are the six types of presupposition. Observational and non-participatory techniques were used to obtain the data. Additionally, the data was analyzed using the pragmatic identity technique and pragmatic competence-in-equalizing data. To get data from the source, a number of procedures are taken. The researchers started by downloading the movie’s script. The researchers next watched the movie on the internet while highlighting the utterances that had the occurrence of presupposition. The result of this research revealed that there were 15 utterances of presupposition in Camp Rock movie. There were existential presupposition with 4 data, factive presupposition with 1 data, lexical presupposition with 5 data, structural presupposition with 4 data, and counterfactual presupposition with 1 data. The most dominant presupposition type appeared in the movie was lexical presupposition, because most of the characters declared meanings which were customarily interpreted with presumptive statement and had another meaning was recognized.